2015
DOI: 10.1152/ajpcell.00275.2013
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 regulates vascular endothelial cell adhesion and tube formation

Abstract: sient receptor potential melastatin 7 (TRPM7) is a nonselective cation channel with an ␣-kinase domain in its COOH terminal, known to play a role in diverse physiological and pathological processes such as Mg 2ϩ homeostasis, cell proliferation, and hypoxic neuronal injury. Increasing evidence suggests that TRPM7 contributes to the physiology/pathology of vascular systems. For example, we recently demonstrated that silencing TRPM7 promotes growth and proliferation and protects against hyperglycemia-induced inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 77 publications
2
24
0
Order By: Relevance
“…Accumulating evidence indicates that TRPM7 is essential for multiple cellular processes, including survival, proliferation and migration in stem cells and endothelial cells via PI3K/Akt pathways . It has been well demonstrated that TRPM7 could inhibit the growth and migration of human umbilical vein endothelial cells (HUVECs) . Instead, inhibited or impaired the expression of TRPM7 could enhance the proliferation and migration, as well as angiogenesis of HUVECs, which might be due to the regulation of NO and the inhibition of autophagy …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that TRPM7 is essential for multiple cellular processes, including survival, proliferation and migration in stem cells and endothelial cells via PI3K/Akt pathways . It has been well demonstrated that TRPM7 could inhibit the growth and migration of human umbilical vein endothelial cells (HUVECs) . Instead, inhibited or impaired the expression of TRPM7 could enhance the proliferation and migration, as well as angiogenesis of HUVECs, which might be due to the regulation of NO and the inhibition of autophagy …”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRPM7/caveolae/lipid raft association may facilitate TRPM7 scaffolding to cell membrane receptors. Increasing evidence has emerged that TRPM7 negatively regulates the function of vascular endothelial cells and reduced level of TRPM7 might facilitate the vascular repair in case of damage through enhanced angiogenic activity, thus suggesting TRPM7 channel as a target for the therapeutic intervention of vascular diseases [175]. TRPA1 channel is present in cerebral artery endothelial cells and mediates endothelium-dependent dilation in response to oxidized lipid metabolites.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Endothelial cells, layers of which form the endothelial lining of the vasculature, express a magnesium transporter (TRPM7) [45]. Low circulating levels of magnesium may lead to endothelial dysfunction through upregulation of this transporter [45, 46]. Further, hypomagnesemia may impair the healing process following vascular injury by regulating endothelial cell migration and proliferation [47].…”
Section: Discussionmentioning
confidence: 99%